Twenty years later: An update to the birds of the biological dynamics of forest fragments project, Amazonas, Brazil - Rutt, Cameron L.; Jirinec, Vitek; Johnson, Erik I.; Cohn-Haft, Mario; Vargas, Claudeir Ferreira; Stouffer, Philip C. (Revista Brasileira de Ornitologia, 2017)
Although species lists from throughout Amazonia have become available, relatively complete inventories based on longterm work remain rare. Longitudinal comparisons at well-studied sites provide the best opportunities for describing communities and identifying changes in regional avifaunas. Within central Amazonia, no region has received as much consistent ornithological coverage as the terra firme forests north of Manaus, Brazil, at the Biological Dynamics of Forest Fragments Project (BDFFP). Here we provide an updated list of the area, including notes on all species added between 1997 and 2017. We recorded 21 species new for the site, most of which (>75%) are birds that prefer várzea or second-growth forest. This brings the cumulative BDFFP list up to 409 species, the majority (66%) of which inhabit primary terra firme forest. Together, this confirms that the regional terra firme community had been well-characterized by the 1990s, and that species additions to the list over the last 20 years are consistent with a changing landscape as urbanization, agriculture, and second-growth spread from Manaus. The final product continues to represent the most complete avian inventory for a single site in all of lowland Amazonia. © 2017, Sociedade Brasileira de Ornitologia. All rights reserved.
Keywords: Avifauna; Bird; Forest; Fragmentation; Neotropical Region; Ornithology; Solid Earth; Species Inventory; Amazon River; Amazonas; Amazonia; Manaus; Aves